Unveiling the masking effect: The role of R&D human capital in collaborative innovation and sustainability - Haidong Lei; Xiaodong Chen; Chaowei Wang; Peng Zhou (Cardiff University, Cardiff Business School, 2025)
Purpose - This research aims to investigate the causal relationships among collaborative innovation, R&D human capital, and sustainable innovation. Emphasize the mediating role of R&D human capital in the link between collaborative innovation and sustainable innovation. Design/methodology/approach - Our research utilizes data from Chinese A-share listed companies spanning 2009 to 2022. We first identify a solid causal relationship between collaborative innovation and sustainable innovation. Then, the existence of a masking effect role of R&D human capital between the two is revealed. Grouped and quantile regression analyses are further employed to explore the heterogeneities of the masking effect across different cooperation types, asset scales, and industries. Findings - Our findings demonstrate that collaborative innovation significantly enhances sustainable innovation through R&D human capital, but the masking effect of R&D human capital slightly dampens this enhancement. The enhancement is evident in inter-firm collaborations but not in industry-university partnerships. It holds across enterprise sizes, but the effect is more pronounced for firms with lower R&D levels. We argue for the importance of prioritizing quality over quantity in collaborative and sustainability. Practical implications - Firms can benefit from human resources (HR) sharing. Policymakers should back human resource integration to boost innovation quality and efficiency. Originality/value - We are the first to study the mediating role of R&D human capital in connecting collaborative and sustainable innovation. While previous studies on the effects of collaboration have mainly focused on the quantity of innovation outcomes, we find that an excessive emphasis on quantity can negatively affect sustainability.
Keywords: O32; 330; Open innovation; R&D human capital; sustainable innovation; mediation effect; industry-university-research